The status and prospects of Intramuros as a tourist attraction - Rodriguez, Elizabeth Plaza. 4 0 16; 5
ABSTRACT: This is a three-level assessment on Intramuros, the first dealt on its present status, the second on the extent this status is addressed by existing tourism plans, and the third on identifying provisions that will improve the tourism potential and prospects of Intramuros. One hundred twenty respondents participated in this investigation. These respondents consisted of thirty (30) government officials, thirty (30) local businessmen, thirty (30) local tourists, and thirty (30) foreign tourists. A scale on tourism potential was used in the data collection conducted in December 1993 and January 1994. In addition, individual interviews were made to authenticate specific information. Existing tourism plans (the Intramuros Urban Development Plan and the Tourism Master Plan (were reviewed and analyzed). Percentage analysis, mean and standard deviation, analysis of variance, F-ratio, and t-test were computed to treat the data statistically. The study revealed that the general assessment about Intramuros is Satisfactory in the economic aspect and Very Satisfactory in the physical aspect and socio-cultural and religious aspects. With the foreign tourists demonstrating a significant difference in their assessment of the Walled City, the findings suggest that so much yet has to be done to improve the tourist attraction of the place. With the various prospects identified in the study, a comprehensive plan was developed and is proposed for field testing and eventful implementation.
Thesis (Ph.D.) -- Pamantasan ng Lungsod ng Maynila, 1995.;A dissertation presented to the faculty of the Graduate School of Management in partial fulfillment of the requirements for the degree Doctor of Business Administration.
Keywords: 2 -- 0; 6; 20; 20; 2